The Function of Coconut Sugar Cluster Establishment for Local Economic Development in Banyuwangi Regency - Cahyantini, Aryntika; Khusaini, Moh.; Pratomo, Devanto Shasta (Institute of Research and Community Service, University of Brawijaya, 2017)
This research was aimed to analyze and to understand (1) factors influencing local economic development of coconut sugar cluster in Banyuwangi Regency; (2) the function of coconut sugar cluster establishment for local economic development, especially for workers absorption and for increasing people income and product innovation in Banyuwangi Regency. Analysis method was quantitative with AHP analysis. The result of research indicated several findings (1) Natural resource was the most influential factor for local economic development in Banyuwangi Regency if compared to human resource, government role, and output. In natural resource, the most determining sub-factor was raw material. For human resource, the most influential sub-factor was worker skill. For the factor of government role, the most influential sub-factor was capitalization. This sub-factor was more advantageous than training and infrastructure. For output factor, the most influential sub-factor was product quality. (2) It must be useful to increase participation, to improve income, and to produce innovation to local communities of Banyuwangi Regency.Keywords: Local Economic Development, Clusters, Coconut SugarÂ